Groundwater Contamination and Remediation - Timothy D. Scheibe (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This Special Issue of Water brings together 10 studies on groundwater contamination and remediation. Common themes include practical techniques for plume identification and delineation, the central role of subsurface processes, the pervasiveness of non-Fickian transport, and the importance of bacterial communities in the broader context of biogeochemistry.